IMPLEMENTASI PRINSIP NEUROSAINCE DALAM KEGIATAN BELAJAR MENGAJAR - Aditya Yoga Syahputra; Vionita; Vava Iman Agus Faisal (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to describe the implementation of Neuroscience principles in teaching and learning activities at SD Negeri Bumireso. The study used a descriptive qualitative approach to obtain an in-depth picture of learning practices that are aligned with the workings of the brain of elementary school students. The research procedure is carried out through the stages of planning, implementation of data collection, data analysis, and conclusion. Data collection techniques include in-depth interviews with teachers as well as direct observation of the learning process in the classroom. The data were analyzed by means of data reduction, data presentation, and thematic conclusions. The results showed that the principles of neuroscience have been applied practically in learning, among others, through the creation of a safe and conducive learning environment, active learning that involves students directly, the provision of positive reinforcement, as well as the Association of learning materials with students’ real experiences. The implementation has an impact on increasing students ' attention, motivation, and involvement in learning. This study shows that the application of Neuroscience principles contributes positively to improving the quality of teaching and learning in primary schools.